ANALISIS TINGKAT KETIMPANGAN PENDAPATAN ANTAR KECAMATAN DI KABUPATEN LOMBOK BARAT - Sahar Sahar (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2018)
The existence of different PDRB values ​​in each region is caused by the success rate of products from leading sectors that are generated to spur economic growth. This study aims to analyze the level of income inequality between sub-districts in West Lombok Regency. This type of research is descriptive with a quantitative approach, the data used in the form of secondary data obtained from the statistical center of West Lombok Regency. The Klassen Typology Analysis Tool is used to find out an overview of the pattern and structure of economic growth in each region. Based on the Klassen typology according to economic growth and per capita income, those included in the fast-growing and fast-growing regions are the Lembar Subdistrict Batu Layar District, Gerung District. Sub-districts included in the fast-developing area are Labuapi Sub-Districts, Kediri District, Lingsar District, Narmada District, and Gunung Sari District. The results of the study stated that there were differences in the classification of districts in West Lombok Regency based on economic growth and per capita PDRB according to the Klassen Typology. Sub-districts included in the underdeveloped areas are Sekotong and Kuripan Districts. In the 2012-2016 observation period with the Williamson inequality index in West Lombok District, the rate of inequality that has started to decline, from 2012 to 2015 for example in 2012 amounted to 0.28336, in 2013 decreased by 0.28335, in 2014 fell again by 0.28258, and in 2015 it dropped to 0.28247, but in 2016 inequality in West Lombok Regency rose again to 0.28277 so the average of the Williamson Index from 2012 to 2016 was 0.28291.